2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00274
|View full text |Cite
|
Sign up to set email alerts
|

To Bundle Adjust or Not: A Comparison of Relative Geolocation Correction Strategies for Satellite Multi-View Stereo

Abstract: The generation of up-to-date accurate 3D models from multi-view satellite images has recently become a hot research topic. A well-known challenge of this problem is to put all cameras into a common frame of reference, since depending on the satellite geopositioning equipment the camera parameters may contain errors of up to tens of meters on the ground. In this context, bundle adjustment based techniques, relying on the identification of a set of tie-points and the correction of the camera models to make them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…However, it depends on detecting and matching a sufficient quantity of accurate correspondences across the multiview images, which is a problem when the study area is restricted to a small test area of interest. Moreover, previous work (Marí et al, 2019) highlighted that post-co-registration of the computed multi-stereo DSMs showed high robustness and accuracy compared to the bundle adjustment for small area scenario. Hence in this paper, no bundle adjustment is conducted before multi-stereo matching;…”
Section: To Bundle Adjustment or Not?mentioning
confidence: 98%
“…However, it depends on detecting and matching a sufficient quantity of accurate correspondences across the multiview images, which is a problem when the study area is restricted to a small test area of interest. Moreover, previous work (Marí et al, 2019) highlighted that post-co-registration of the computed multi-stereo DSMs showed high robustness and accuracy compared to the bundle adjustment for small area scenario. Hence in this paper, no bundle adjustment is conducted before multi-stereo matching;…”
Section: To Bundle Adjustment or Not?mentioning
confidence: 98%
“…Mismatches in the feature track observations can strongly undermine the bundle adjustment performance, leading to failure or strong biases [3,29]. We remove erroneous matches by means of a distance ratio test with a relative threshold of 0.6 [28].…”
Section: Pairwise Matchingmentioning
confidence: 99%
“…Similarly to [29], the object coordinates of the tie point that projects onto each feature track are initialized by triangulating all the pairwise matches of the track and taking the mean of the resulting 3D locations (Algorithm 3). The RPC triangulation algorithm from [15], denoted by Triangulate in Algorithm 3, is employed to triangulate keypoint correspondences with the RPC camera models.…”
Section: Feature Tracks Triangulationmentioning
confidence: 99%
See 2 more Smart Citations